In Vitro and In Vivo Evaluation of Kai-Xin-San Polysaccharides: Antioxidant, Anti-Inflammatory, and Anti-Alzheimer's Disease Activities - Xiong, Yongchang; Zhou, Lifen; Zhang, Min; Liang, Jian; Zheng, Qin; Chen, Ying; Cai, Zhinan; Yu, Lide; Yuan, Jinbin (Current Neuropharmacology, 2025)
<span class=
Keywords: Kai-Xin-San